Dynamic cohort study evaluating metabolic predictors of influenza vaccine immune response in older adults - Sadarangani, Sapna (2023)
Immunosenescence (age-related immune dysfunction) and inflamm-aging contribute to suboptimal immune responses in older adults to standard-dose influenza vaccines, which may be exacerbated in those with metabolic co-morbidities. We sought to investigate metabolic factors/predictors of influenza vaccine immune response in an older adult (age ≥65 years) cohort in Singapore, where influenza typically circulates year-round. The primary outcome for the DYNAMIC prospective cohort study was haemagglutination-inhibition titer (HAI) response to each of the trivalent inactivated influenza vaccine strains at day 28 (D28) compared to baseline (D0), as assessed by seroconversion and D28/D0 log2 HAI fold rise. Baseline blood samples were tested for total Vitamin D (25-(OH) D) levels. We enrolled 234 participants in June-Dec 2017. Two hundred twenty completed all study visits. The median age was 71 [IQR 68-75] years, 67 (30.5%) had diabetes mellitus (DM), and the median BMI was 24.9 [IQR 22.2-27.8] kg/m2. Median baseline totals 25-(OH) D was 29 [IQR: 21-29] ng/ml. Age, DM, obesity, and baseline 25-(OH) D were not associated with HAI fold rise in multivariable analysis. More recent prior influenza vaccination and higher baseline HAI titers were associated with lower HAI fold rise for influenza A/HK/H3N2. Physical activity was associated with a higher HAI fold rise for influenza A/HK/H3N2 in a dose-response relationship (p-test for trend = 0.015). Older adults with well-controlled metabolic co-morbidities retain HAI response to the influenza vaccine, and physical activity had a beneficial effect on immune response, particularly for influenza A/HK/H3N2.